Popularity Abracadabra and Communication Ethics on Social Media (A Study of Rhetoric on the Content of YouTube Account @Kaesang) - Andika Mustaqim (CV. AFDIFAL MAJU BERKAH, 2023)
Communication ethics is an important factor for a politician in conveying content on social media. Ethics is also a guide in gaining popularity, especially for politicians who want to fight for power. This study aims to examine the ethics of communication on Kaesang Pangarep's YouTube account. Using Habermas's (1984) communication ethics approach, this study examines the various approaches to popularity-based communication ethics by Kaesang. By using a qualitative approach, content analysis is a research method that is applied with an emphasis on descriptive. This research finds many novelties in the study of communication ethics. Kaesang adheres to communication ethics such as communicative action and dramaturgical approach. Kaesang also displays honesty by showing originality as an effort to construct legitimacy. Then, the research states that there is no violation of the validity of the truth, determination and honesty that Kaesang. To apply communication ethics, this study reveals the popularity of abracadabra by Kaesang, namely using caution in rhetoric and polite language style